The Effect of Using Brainstorming Methods on Students Critical Thinking Ability on Science Learning in Middle School - Venny Dwinta Nurikhwan; Arif Sholahuddin; Maya Istyadji (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2023)
A research was conducted bolawins on students' critical thinking skills in science learning in SMP. This study aims to determine the differences in the critical thinking skills of students who learn with the brainstorming method in class VII students of SMP Negeri 6 Banjarmasin in the 2018/2019 academic year. This study used a quasi-experimental method using a pretest-posttest nonequivalent control group design. The sample of the study was class VII A students consisting of 30 students as the experimental class and class VII G students consisting of 30 students as the control class. The sampling technique used was cluster random sampling. Data collection techniques using test techniques. The data analysis technique used the t-test to analyze differences in the critical thinking skills of students in the experimental and control classes, and descriptive analysis to describe the differences in the level of critical thinking skills between students who used the brainstorming and expository methods. The result showed that there was a significant difference between the experimental class and the control class as indicated by the results of the t-test from the price Tcount > Ttable (2,41 > 2) and there was a difference in critical thinking skills between the experimental class and the control class as indicated by the percentage value, posttest experimental class namely 82,08% and control class 71,38%.Keywords: Brainstorming, Expository, Critical Thinking, Science